Influence of thermooxidative aging on the static and dynamic mechanical properties of long‐glass‐fiber‐reinforced polyamide 6 composites. Issue 3 (9th September 2013) - Zuo, Xiaoling; Zhang, Kaizhou; Lei, Yang; Qin, Shuhao; Hao, Zhi; Guo, Jianbing
ABSTRACT The static and dynamic mechanical properties, thermal behaviors, and morphology of pure long‐glass‐fiber‐reinforced samples [polyamide 6 (PA6)/long glass fiber (LGF)] with different thermal exposure times at 160°C were studied by comparison with stabilized samples in this study. The aging mechanism of the PA6/LGF samples under heat and oxygen was studied with the methods of thermal Fourier transform infrared (FTIR), differential scanning calorimetry, dynamic mechanical analysis, scanning electron microscopy (SEM), and so on. The results indicate that the static mechanical strength, melting temperature, and crystallization temperature decreased because of the decomposition of the macromolecular chain of PA6 resin and the debonding of the interface between the glass fibers and matrix. The glass‐transition temperature and crystallinity also increased and decreased, respectively, after aging. The macromolecular chain decomposition dominated in the subsequent aging process; this resulted in many sharp and brittle microcracks appearing on the surfaces of the aged samples, as shown by SEM and the FTIR spectra. The existence of stabilizers endowed the PA6/LGF composites with better retention of static and dynamic mechanical properties. The reason was that the metal ions of the copper salt antioxidant acted as an anti‐aging catalyst in the reinforced PA6 system. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39594.